2016
DOI: 10.1016/j.applthermaleng.2015.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of R448A and R450A as low-GWP alternatives for R404A and R134a using a micro-fin tube evaporator model

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The ODP value of two gases according to equation (8) was that SF 6 gas has a value of 0.08 times that of CO 2 gas, while the ODP value of CF 3 CHCl 2 gas had a value of 0.016 times the gas from CO 2 gas. c. The Alt value of two gases according to equation (9) was that SF 6 gas had an Alt value of 3200 years while CF 3 CHCl 2 gas had an Alt value of 1.5 years. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The ODP value of two gases according to equation (8) was that SF 6 gas has a value of 0.08 times that of CO 2 gas, while the ODP value of CF 3 CHCl 2 gas had a value of 0.016 times the gas from CO 2 gas. c. The Alt value of two gases according to equation (9) was that SF 6 gas had an Alt value of 3200 years while CF 3 CHCl 2 gas had an Alt value of 1.5 years. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The R134A, is a generation of HFC that possess zero ODP and a GWP = 1800 [14], that was developed for the R22, but it has a low refrigerant effect. The R513A, R515A, R450A, R456A were developed to be alternatives to R134, but the performances of all refrigerants were nearly [15][16][17][18], subsequently, the refrigerant developed to the R404A. The fourth generation R404A was the baseline for this research, and is currently the most used refrigerant, as shown Figure 5 below [7].…”
Section: Evolution Of the Refrigerantmentioning
confidence: 99%
“…The R134A, is a generation of HFC that possess zero ODP and a GWP = 1800, that was developed for the R22, but it has a low refrigerant effect [38]. The R513A, R515A, R450A, R456A were developed to be alternatives to R134, but the performances of all refrigerants were nearly, subsequently, the refrigerant developed to the R404A [11][12][13][14]. The fourth generation R404A was the baseline for this research, and is currently the most used refrigerant, as shown Figure 5 below [6].…”
Section: Evolution Of the Refrigerantmentioning
confidence: 99%